Antioxidant and nitric oxide inhibition activities of myristica fragrans essential oil in RAW 264.7 Cells - Aulia Rahmatun Nufus; Nirwana Lazuardi Sary; Fauzul Husna (AcTion: Aceh Nutrition Journal, 2025)
The excessive production of free radicals, such as Nitric Oxide (NO), initiates several diseases. Compounds of nutmeg oil (MFEO) have been reported to exhibit antioxidant activity. This study aimed to evaluate the antioxidant activity, cytotoxicity, and NO inhibitory potential of MFEO. This experimental study was conducted using the MFEO obtained from plantations in South Aceh Regency, Indonesia. The antioxidant activities were tested using the ABTS and FRAP tests, cytotoxicity test used micro-tetrazolium solution and NO production inhibition were carried out on RAW 264.7 cells used Griess Reagent. The IC50 values were determined using linear regression statistical analysis (p<0,05). Results, the IC50 values of MFEO using the ABTS method were 8,400 ppm and 24,949 ppm, respectively, using the FRAP method. These results indicate that MFEO has a very weak antioxidant activity compared to Trolox and ascorbic acid. An MFEO concentration of 250 ppm showed a cell viability of more than 50% (75,57%), and the ability to inhibit NO production began to be shown at an MFEO concentration of 50 ppm (7,5%). The antioxidant activities of MFEO were very weak and MFEO concentrations starting from 50 ppm inhibited NO production, and up to a concentration of 250 ppm, more than 50% viability of RAW 264.7 cell. In conclusion, MFEO needs higher concentrations than Trolox and ascorbic acid for strong antioxidant effects. At lower doses, it remains safe for RAW 264.7 cells and effectively reduces NO production.